Meneleaah Kembali Bangkitnya Ekonomi Islam: Analisis antara Peluang dan Tantangan - Hosen Hosen (Prodi Ekonomi Syariah STAI Syaichona Moh. Cholil Bangkalan, 2022)
The development of Islamic economics education is not only felt by Muslim-majority countries, but also in developed countries such as England, which are starting to be interested in studying Islamic economics. Realizing sharia-based economic education at the pre-college level or middle school period is very necessary because the process of absorbing sharia economic values ??into life activities will be more effective if taught earlier before college. The integration of early Islamic economic education will be outlined in an activity in the form of sharia-based cooperative-based extracurricular activities. So that the output of integrating Islamic economics education with student cooperative extracurriculars will not only be able to immediately become actors in sharia business institutions and also do not rule out the possibility for SMA/MA graduates who apply this to continue their education to the Higher Education level to become easier. This method uses a type of library research (library research). The data collection technique used documentation, namely, related to the theme